Electrical conductivity and relaxation in lithium-doped barium vanadate glasses investigated by impedance spectroscopy. (February 2023) - Goel, Parul; Honnavar, Gajanan V.; Ramesh, K.P.
Abstract: We present herein a detailed study of the electric and dielectric properties of glasses with the composition 60V2 O5 –(40– x )BaO– x Li2 O, where x  = 10, 15, 20, or 25 mol%. The conduction and relaxation mechanisms have been studied by impedance spectroscopy over the frequency range from 40 Hz to 10 MHz and at various temperatures. With constant transition metal oxide content, the conductivity variation in the glasses is assumed to be mainly due to an ionic contribution. The dependence of electrical conductivity on frequency has been analysed using Jonscher's power law. Properties of the glasses, such as electric modulus loss and relaxation mechanism, have been analysed in terms of electric modulus using the Kohlrausch–William–Watts (KWW) equation, which describes the relaxation behaviour of the mobile ions as non-Debye in nature. Scaling of ac conductivity and electric modulus data has shown that conductivity relaxation is independent of temperature. The non-monotonic variation in the stretching parameter β has been found to show a positive correlation with various activation energies, namely electrical activation energy, relaxation activation energy, and the activation energy from the Anderson–Stuart model. The anomalous behaviour of activation energy with respect to conductivity has been substantiated through structural insight. The conductivity was found to be highest in glasses with 25 mol% Li2 O, while coupling between the mobile ions was best for glasses with 20 mol% Li2 O. Graphical abstract: Image 1 Highlights: Electric and dielectric properties of glasses 60V2 O5 -(40-x)BaO-xLi2 O, using impedance spectroscopy as tool. Dependence of electrical conductivity on frequency analysed using Jonscher's power law showed increase in dc conductivity with increasing alkali content. The relaxation mechanism was analysed in terms of electric modulus using the Kohlrausch-William-Watts (KWW) equation. The scaled plots indicate temperature independent relaxation mechanism. The stretching parameter β showed a positive correlation with various activation energies.